Effects of non-shunting operation on azygos venous blood flow in cirrhotic patients. Issue 10 (October 1989) - Kokudo, N; Kawasaki, S; Ohashi, K; Sakamoto, H; Koyama, H; Sanjo, K; Idezuki, Y
Abstract : Azygos venous blood flow and other haemodynamic parameters were measured in 14 cirrhotic patients to investigate the effects of a non-shunting operation, oesophageal transection with paraoesophagogastric devascularisation. Azygos venous blood flow measured by the local continuous thermal dilution method was significantly reduced by 13.8% after the operation (428 (41) v 369 (33) ml/min). Hepatic venous pressure gradient (HVPG) was also significantly decreased from 14.5 (0.8) to 12.8 (0.7) mmHg (-11.8%). Cardiac output and routine liver tests did not change remarkably postoperatively. In this haemodynamic study before and after non-shunting operation, moderate but significant decreases were seen in azygos venous blood flow and portal pressure (HVPG), without substantial changes in systemic circulation. This suggests that blood flow through the portosystemic collaterals other than oesophageal varices may be decreased but still adequate after the operation. Well preserved portosystemic collaterals without oesophageal varices are thus considered an optimally balanced state after non-shunting operation.